Membangun Keteguhan Iman di Tengah Badai dengan Meneladani Perjuangan Dakwah Rasulullah di Makkah - Nadhira Zahra Ikrima; Nada Nofrianti; Ridwal Trisoni; Muhamad Yahya (4, 2025)
The background of this study stems from the condition of contemporary Muslim society, which faces a spiritual crisis, moral decay, and the dominance of materialism that weakens the foundations of faith. This research positions itself within the field of Islamic da'wah history and spirituality studies, focusing on two main aspects: the characteristics of Meccan society at the beginning of Islam’s spread and the substance and strategies of the Prophet Muhammad’s da'wah during that period. In this article, the discussion is conducted using a qualitative-descriptive approach with an analysis of classical sources such as the Sīrah Nabawiyyah, hadith, and Makkiyah Qur’anic verses. Meccan society is portrayed as a community with strong social structures but overshadowed by polytheism, social inequality, and tribal fanaticism that rejected the values of monotheism (tawḥīd). In this context, the Prophet implemented a gradual da'wah strategy focusing on the development of faith (ʿaqīdah), the cultivation of patience (ṣabr), and the formation of noble morality through personal example. The findings of the study indicate that the essence of the Prophet’s da'wah in Mecca was not merely about conveying theological teachings but also about shaping the spiritual and social character of the believing community. From this struggle, it can be concluded that steadfastness in faith grows through a deep understanding of tawḥīd, patience in facing trials, and commitment to divine values that serve as the foundation of Islamic civilization amid the storms of life. Abstrak Latar belakang permasalahan berakar pada kondisi umat Islam masa kini yang dihadapkan pada krisis spiritual, dekadensi moral, dan dominasi materialisme yang melemahkan fondasi keimanan. Penelitian ini menempatkan diri dalam ranah kajian sejarah dakwah dan spiritualitas Islam, dengan fokus pada dua aspek utama: karakteristik masyarakat Makkah pada awal penyebaran Islam serta substansi dan strategi dakwah Rasulullah pada periode tersebut. Dalam artikel ini, pembahasan dilakukan melalui pendekatan kualitatif-deskriptif dengan analisis terhadap sumber-sumber klasik seperti Sirah Nabawiyyah, hadis, dan ayat-ayat Makkiyah. Masyarakat Makkah digambarkan sebagai komunitas yang memiliki tatanan sosial kuat namun diliputi kemusyrikan, kesenjangan sosial, dan fanatisme kabilah yang menolak nilai tauhid. Dalam konteks ini, Rasulullah menerapkan strategi dakwah bertahap yang berfokus pada pembinaan akidah, penanaman nilai-nilai kesabaran, dan pembentukan moralitas luhur melalui keteladanan pribadi. Hasil kajian menunjukkan bahwa substansi dakwah Nabi di Makkah bukan hanya tentang penyampaian ajaran teologis, tetapi juga pembentukan karakter spiritual dan sosial umat yang beriman. Dari perjuangan tersebut dapat disimpulkan bahwa keteguhan iman tumbuh melalui pemahaman mendalam terhadap tauhid, kesabaran menghadapi ujian, serta komitmen terhadap nilai-nilai ilahi yang menjadi fondasi peradaban Islam di tengah badai tantangan kehidupan